2018
DOI: 10.15294/biosaintifika.v10i2.12600
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Problem-Based Learning Module as An Instructional Tool in Improving Scientific Argumentation Skill

Abstract: Scientific argumentation skill required to be mastered in this era. Unfortunately many students still have strunggle improving their scientific argumentation skills. This study was aimed at describing the effectiveness of ecosystem module grounded in Problem-Based Learning in improving scientific argumentation skills. This research was part of the field testing of R&D, a research and development previously conducted. Research participants included tenth grade senior high school students. Two classes were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
(15 reference statements)
1
3
0
3
Order By: Relevance
“…It indicates that PBL model helped in increasing the level of students' scientific argumentation skills. This is similar with Nurinda, et al [28], problem-based learning can be used to improve students' scientific argumentation skills. According to Ponimin, et al [29], the scientific argumentation skill in the experimental class (using the PBL model) were better than the control class (non-PBL).…”
Section: Discussionsupporting
confidence: 71%
“…It indicates that PBL model helped in increasing the level of students' scientific argumentation skills. This is similar with Nurinda, et al [28], problem-based learning can be used to improve students' scientific argumentation skills. According to Ponimin, et al [29], the scientific argumentation skill in the experimental class (using the PBL model) were better than the control class (non-PBL).…”
Section: Discussionsupporting
confidence: 71%
“…Some studies also showed a decline in scientific argumentation skills in general (Nurinda et al, 2018;Sekerci and Canpolat, 2017). Several studies have found students' weakness in thinking skills in general and logical thinking in particular (Fah, 2009;Powell, 2000;Al-Hadrami, 2012;Al-Afifi and Ambusaidi, 2014).…”
Section: Research Problem and Questionsmentioning
confidence: 99%
“…Interaksi yang terjadi pada tahap conceptualization mendorong siswa pada tingkat perkembangan aktual untuk dapat mencapai tingkat perkembangan potensial, sehingga dapat memfasilitasi siswa untuk mengembangkan kemampuan argumentasi ilmiah aspek claim. Hal ini didukung oleh pernyataan Nurinda et al, (2018a) bahwa komponen argumentasi claim diperoleh siswa setelah mereka dihadapkan dengan permasalahan atau konflik.…”
Section: Argumentasi Ilmiah Tertulis Aspek Claimunclassified
“…Pemahaman konsep siswa menjadi lebih baik ketika siswa menemukan sendiri konsepnya, pemahaman konsep yang baik dapat meningkatkan kemampuan argumentasi ilmiah aspek reasoning. Hal ini didukung oleh pernyataan Nurinda et al, (2018a) bahwa komponen argumentasi reasoning dapat dilatihkan melalui kegiatan analisis hasil pengamatan atau penyelidikan dan kegiatan diskusi.…”
Section: Argumentasi Ilmiah Tertulis Aspek Reasoningunclassified